Co-creation and well-being in tourism - Correia, Antónia; Kozak, Metin, 1968-; Gnoth, Juergen; Fyall, Alan (Springer, 2017)
This book offers a wealth of new views and interpretations of well-being in tourism, emphasizing the role that co-creation - the creation or enhancement of value through tourist engagement with tourism providers and other tourists - is increasingly playing in enriching tourist experiences. A combination of theoretical and empirically based contributions relating to various tourism contexts shed light on existing and potential contributions of tourists and destination providers to tourist well-being. Readers will find novel and compelling insights into both the very nature of wellbeing as perceived by the tourist and the opportunities that are emerging as tourists become savvy decision-makers capable of activating their own networks and resources in order to shape their experiences. The book will be of interest for all who wish to learn more about the character and the construction of well-being within tourism, the relationship of well-being to a range of factors, and the ways in which tourism operators can assist tourists in creating high-value experiences.
Keywords: Tourism.; Tourism -- Marketing.; elektronické knihy; electronic books